Short Communication: Terpenoids isolated from Lansium domesticum fruit peel induce apoptosis and cell cycle arrest in T-47D cell lines - KHUSNUL FADHILAH; SUBAGUS WAHYUONO; PUJI ASTUTI (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Fadhilah K, Wahyuono S, Astuti P. 2022. Short Communication: Terpenoids isolated from Lansium domesticum fruit peel induce apoptosis and cell cycle arrest in T-47D cell lines. Biodiversitas 23: 1167-1171. One of the characteristics of cancer cells is uncontrolled proliferation. This can be caused by aberrant in the proteins that play a role in the process of apoptosis and cell cycle. Lamesticumin A and 2-ethyl,3-(1’-hydroxy-2’-menthene) propenal have been isolated from ethyl acetate extract of L. domesticum fruit peel had cytotoxicity against T-47D cells. However, the study on how these terpenoids induce cell death is still unknown. Flow cytometry analysis was carried out to evaluate the effect of the compounds in cell cycle modulation and apoptotic induction. The terpenoid compounds induced apoptosis and cell cycle arrest in S phase in a dose dependent manner. Compound 1 synergized the effect of doxorubicin in inducing cell death through mechanism involving the cell cycle. Compound 1 revealed better activity in killing T-47D cells rather than compound 2. Further studies are needed to explore the potential of these compounds in promoting cell death of breast cancer.